DANCE FILM FOR THE NEEDS OF THE NATIONAL STUDENT ARTS COMPETITION FESTIVAL (FLS2N) AT SMP NEGERI 3 DEPOK - Amelia Febrina; Nursilah; Winiar Garnea; Anjani Ayu Rizki Ramadhani (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
FLS2N is a forum for students to develop interests and talents in the field of arts and culture and compete to reach the peak of achievement. Through this program, it is hoped that students will be able to develop ideas and creativity in the arts from an early age to create self-confidence in their abilities and explore various potential intelligence. The 2023 FLS2N dance competition will be held by recording dance material in the form of a dance film with various provisions in accordance with the guidelines for recording dance films. In this case, we will review the Leuwi Abyudaya Dance Film created by the PKM PM Team as a form of community service for SMP Negeri 3 Depok. The author uses the creation method according to Alma M Hawkins, where this method consists of the Sensing, Feeling, Imaging, Transforming, Forming process, and use the cinematography composition method by Kurt Lancaster that consist of shot sizes and lenses, camera height and angle, camera motion, focal depth of field, light and dark, line and linear perspective, layers, weight, color, dan texture shot sizes and lenses, camera height and angle, camera motion, focal depth of field, light and dark, line and linear perspective, layers, weight, color, dan texture.